2006
DOI: 10.1007/s10495-006-0191-9
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide induces apoptosis via a peroxisome proliferator-activated receptor γ-dependent pathway

Abstract: Both of ceramide and PPARgamma ligand can trigger cancer cell apoptosis. We here show that C2-ceramide can modulate PPARgamma expression level and its transcriptional activity and results in apoptosis in HT29 cells. Administration of PPARgamma specific antagonist GW9662 partially prevents HT29 cells from apoptosis. Furthermore, MAP kinase pathway provided a potential modulation mechanism for PPARgamma pathway related with ceramide. Our results are the first to demonstrate that C2-ceramide induces apoptosis via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Activation of PPARγ by its ligands can induce growth inhibition and cytotoxicity in human prostate cancer cells, colon cancer cells and liposarcoma cells, and their biological activities are attributed to inhibition of proliferation and induction of apoptosis by PPARγ [21,22] . We have previously shown C2-ceramide could induce apoptosis via a PPARγ dependent pathway in human colon cancer HT29 cells [14] . To examine whether the PPARγ pathway was involved in the modulation of cell cycle arrest induced by ceramide in human hepatocarcinoma Bel7402 cells, the luciferase reporter of PPRE3x-tk-luc was transfected and luciferase activity was assayed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Activation of PPARγ by its ligands can induce growth inhibition and cytotoxicity in human prostate cancer cells, colon cancer cells and liposarcoma cells, and their biological activities are attributed to inhibition of proliferation and induction of apoptosis by PPARγ [21,22] . We have previously shown C2-ceramide could induce apoptosis via a PPARγ dependent pathway in human colon cancer HT29 cells [14] . To examine whether the PPARγ pathway was involved in the modulation of cell cycle arrest induced by ceramide in human hepatocarcinoma Bel7402 cells, the luciferase reporter of PPRE3x-tk-luc was transfected and luciferase activity was assayed.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous study, we reported that C2-ceramide could activate PPARγ transcription activity in human colon cancer HT29 cells [14] . In this study, as shown in Figure 3A, C2-ceramide could also markedly activate the transcriptional activity of PPARγ in hepatocarcinoma Bel7402 cells.…”
Section: Cdk7 and Pparγ Pathways Involved In Cell Cycle Arrest Inducementioning
confidence: 94%
“…A well establish pharmacological effect of NSAIDs is inhibition of prostaglandin synthesis by inhibiting cyclooxygenase (COX) activity [12]. NSAIDs induce COX-2-dependent apoptosis by activating PPARs (peroxisome proliferator activated receptors), intracellular receptors that modulate apoptosis in a variety of cell types [13], increasing cellular concentrations of arachidonic acids, a substrate of COX-2, leading to conversion of sphingomyelin to ceramide, a potent apoptosis inducer [14,15], or altering mitochondrial permeability and cytochrome c release [16]. NSAIDs also induce apoptosis via COXindependent pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Endocrine organs targeted by EDCs include the reproductive organs, heart, pancreas, thyroid, parathyroid, adrenal glands, hormone dependent metabolic system (pancreas and liver) and effects on brain function. Particular interest in EDCs such as phthalates in the regulation of the PPAR gamma (nuclear receptors) in adipose tissue indicates that they play an important role in the induction of obesity [114]- [119] similar to ceramide-PPAR interactions in cellular apoptosis and insulin resistance [10] [120]. The effects of EDCs on Sirt1-PPAR (alpha or gamma) interactions and their effects on the endocrine system have been reported with endocrine disorders linked to chronic diseases connected to appetite dysregulation and behavioural disorders.…”
Section: Endocrine Disruptors As Risk Factors For Obesity and Chronicmentioning
confidence: 99%